2003
DOI: 10.1080/10673220303950
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Therapy and Pharmacotherapy for Depressed Patients with or without Personality Disorders

Abstract: In general, depressed patients with personality pathology--Axis II disorders--respond less well or less quickly to the various kinds of individual treatment that are available, whether pharmacotherapy, psychotherapy, or both combined. This article sets forth the results of a six-month, randomized clinical trial of antidepressants and combined therapy in ambulatory patients with major depression and a baseline score of at least 14 on the 17-item Hamilton Rating Scale for Depression (HAM-D-17). The presence or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 20 publications
2
36
0
4
Order By: Relevance
“…Many authors have found that concomitant personality disorders have negative effects on the treatment outcome of patients with major depression, both on depressive symptoms and on social functioning (51)(52)(53)(54). A study by Kool and others compared combined treatment and pharmacotherapy of depression, examining the effect of personality disorders on differences in clinical response (26). In patients with concomitant personality disorders, combined therapy was superior to pharmacotherapy in measures of global psychopathology, depressive symptoms, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have found that concomitant personality disorders have negative effects on the treatment outcome of patients with major depression, both on depressive symptoms and on social functioning (51)(52)(53)(54). A study by Kool and others compared combined treatment and pharmacotherapy of depression, examining the effect of personality disorders on differences in clinical response (26). In patients with concomitant personality disorders, combined therapy was superior to pharmacotherapy in measures of global psychopathology, depressive symptoms, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The psychotherapy consisted of sixteen sessions of short-term, supportive PDT. A range of trials and studies have demonstrated its effectiveness in the treatment of depression [7,9,38,42,43,44,45,46,47,48,49,50,51,52]. The first eight sessions took place weekly, the last eight fortnightly.…”
Section: Methodsmentioning
confidence: 99%
“…There is some controversy on the response of depressed patients with personality disorders to individual treatment. Some found that their response to the combination of psychotherapy and treatment with antidepressants is superior compared with antidepressant treat-ment alone [31] , while others found that patients with long-term psychodynamic psychotherapy alone improved more on the HAM-D score than psychodynamic psychotherapy combined with medication [32] . Therefore, the assessment of personality disorders and defensive functioning could be useful in choosing between various treatments for depression.…”
Section: Discussionmentioning
confidence: 99%